Predictors and portfolios over the life cycle - Kraft, Holger; Munk, Claus; Weiss, Farina (Journal of Banking & Finance, 2019)
In a calibrated consumption-portfolio model with stock, housing, and labor income predictability, we evaluate the welfare effects of predictability on life-cycle consumption-portfolio choice. We compare skilled investors who are able to take advantage of all sources of predictability with unskilled investors ignoring predictability. For an unskilled investor the certainty equivalent of wealth is 0.3–6.8% lower than for a skilled investor, depending on the market entry date. We also determine the effect of luck to enter the market at a favorable time. Across market entry dates, skilled but unlucky investors can lose up to 15.4% compared to unskilled but lucky investors.